The Effect of Viral Marketing and Celebrity Endorsement on Buying Decision of Beauty Products at Tiktok Shop (Study on Generation Z Women) - Nizar Alam Hamdani; Reni Fitrianti; Hedi Cupiadi; Shinta (Migration Letters, 2023)
Purpose: The evaluation of the impact of Viral Marketing is the subject at hand and Celebrity Endorsement on the Decision to Buy Beauty Products at the Tiktok Shop. Design/methodology/approach: This study uses a quantitative method with an explanatory approach. Data collection techniques used field research (surveys, interviews, questionnaires) and library research by reviewing (journals, books, and online information). The technique employed for sampling was non-probabilistic and purposive sampling with a research sample of 97 respondents. Then the data analysis tool uses PLS-SEM with SmartPLS 3.0 software. Finding: The study’s results with descriptive analysis stated that Viral Marketing, Celebrity Endorsements, and Buying Decisions for Beauty Products at the Tiktok Shop had good criteria. Meanwhile, the results of the influence analysis stated that Viral Marketing had a positive and significant effect on the Buying Decision of Beauty Products at the Tiktok Shop, and Celebrity Endorsements had a positive and significant impact on the Buying Decision of Beauty Products at the Tiktok Shop. Practical Implications: The research results are expected to serve as input and consideration for sellers or online businesses using Viral Marketing and Celebrity Endorsement strategies to help achieve the maximum economic potential of Beauty Products offered at the Tiktok Shop.